Possibilities of direct production of superheavy nuclei with Z=112-118 in different evaporation channels; Physics Letters B; Vol. 809 - Hong J. Juhee; Adamyan G. G. Gurgen Grigorjevich; Antonenko N. V. Nikolay Viktorovich; Jachimowicz P. Piotr; Kowal M. Michal (2020, 2020)
Title screen